Promises, pyramids and prisms: Reimagining postgraduate funding - Bradbury, J. (South African Journal of Higher Education, 2023)
The promises of upward mobility and social transformation are intertwined with the story of higher education in South Africa. In the years leading up to and in sync with the democratic moment of 1994, multiple selection programmes and academic development projects engaged with questions of potential (e.g., Yeld 2007; Miller 1992) particularly in relation to the inequalities of apartheid schooling and implications for higher education. While access and success have been widened in the decades since, and participation rates are more demographically representative, #FMF and #RMF challenged the myth of meritocracy. In a disillusioning political present, higher education resembles a giant pyramid scheme in which the investment of many delivers results for only a “lucky” few, particularly the higher up the ladder one ascends (Bradbury 2022). This prioritisation of the privileged continues despite official labour surveys demonstrating that each step along the higher education degree path increases individual employment prospects and contributes to socioeconomic productivity. The focus of this article is on funding for postgraduate students who represent the intellectual future both within the academy and beyond, developing high level skills for the knowledge economy to solve the “wicked problems” of the 21st century. Inherited funding models reward individual excellence, treating students as isolated individuals, falsely assuming supportive middle class family networks and conceiving of study years as a temporal sequestration from communal responsibilities and projected future working life. In reality, the borders between home and campus, between studies and work, between (extended) childhood and adulthood, are far more porous. These funding models are unsustainable, irrational and unethical, and premised on “cruel optimism” (Berlant 2011) rather than the promise of radical forms of hope. The article presents some pragmatic possibilities for reimagining funding for postgraduate studies in South Africa in the present. It is however imperative that these responses attend to both the past and the future to create conditions of “freedom in security” (Manganyi 1973) in which individual and collective potential can be actualised for a more equal future.